Deadlock in maintaining Wosi Rendani protected forest in Manokwari Regency, West Papua - Mahmud, Mahmud (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2021)
Protection forest covers 29.7% of the state forest area, which has role a very important. The research aims to determine what factors cause the deadlock in maintaining the Wosi Rendani Protection Forest (HLWR). The research method used is descriptive technique, development and evaluative method. The results showed that the local and central government negligence in determining the prolonged HLWR made the area of the decrease drastically. The formation of the province of West Papua with the provincial capital in Manokwari, the impact along the Drs.Esau Sesa st., there is not an inch of empty land. Low community participation, they feel ignorant of the existence of forests in protecting, protecting and maintaining HLWR. The diversion of the transportation route connecting Sowi with Jalan Trikora Rendani on the east side of the HLWR has made the roads filled with built-up areas.. Community empowerment low around make owners of customary rights to sell the land, regardless of protected fores. We believe that the deadlock in the designation of protected forests can provide new insights so that they are not repeated in policies to maintain / release protected forests in Indonesia and even the world.